Heterostructure of Titanium Dioxide Nanotube/Graphene Nanoplatelet with Enhancing Photocatalytic Activity - Mai, Vo Quang; Hao, Vo Chi; Tho, Nguyen Huu; Sang, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 3DO - 10.25073/2588-1140/vnunst.4947, 2020)
In this study, the composite of titanium dioxide nanotube (TNT) and graphene nanoplatelet was hydrothermally synthesized in a sodium hydroxide solution. Morphological and crystalline properties of the synthesized samples were analyzed by transmission electron microscopy (TEM), X-ray differactometry (XRD), and Raman spectroscopy. Optical properties were investigated by UV-Vis diffuse reflextance spectra (DRS) where optical bandgap was determined. Photocatalytic activity of the synthesized samples was evaluated through the degradation of methylene blue in the solution under direct sunlight irradiation. The result showed the enhancement of photocatalytic activity in the composite sample in compare to the bare TNT. After 120 min of irradiation, the photocatalytic efficiency of the composite and TNT was ~95% and 63%, respectively. Mechanism of enhanced activity was supported by DRS measurements in which the composite showed the higher visible light absoption and lower bandgap value. Optical bandgap of the sGr/TNT composite was about 3.25 eV which was notably reduced in compare to that of the bare TNT of ~3.68 eV.